An Improved Extended 2-Point Super Class of Block Backward Differentiation Formula for Solving Stiff Initial Value Problems - Adamu Abdulrahman; Musa Hamisu (Journal of Science and Technology, 2025)
A novel, enhanced two-point block backward differentiation formula has been devised for solving stiff initial value problems of ordinary differential equations, boasting superior stability properties, including zero-stability and near A-stability. Comparative analysis reveals its exceptional accuracy and efficiency, outperforming some existing methods, thereby positioning it as a viable alternative solver for addressing stiff initial value problems.